A Multi-Group Analysis of Salient Determinants of E-government Implementation Success in Developing Countries. A Study of Uganda and Tanzania - Kagoya, Sumaya M.; Tinali, Gerald Zachary Paga; Caine, Jamie (University of Dar es Salaam Library Journal, 2022)
In-spite of the presence of all-encompassing synopsis of e-government implementation determinants in Most developed countries, a multi-group analysis of contextual salient determinants is missing in DCs. When it comes to implementation of e-government projects, most developing countries just copy already implemented projects from MDCs and paste without editing to suit their nations. This has resulted into massive failure of such e-projects partly due to failure to account the salient determinants of e-government implementation success which vary from one nation to another. This study bridges this knowledge gap by examining a multi-group analysis of contextual salient determinants of e-government implementation success in Uganda and Tanzania. Structured questionnaires were used to pucker quantitative data from the 72 employees and 64 employees from Ministries of finance and planning in Uganda and Tanzania respectively. PLS €“SEM aided by SmartPLS 3 were used for analysis. Using UTAUT and empirical evidence, a model was proposed. Findings indicate insignificant results for information system attribute while all other constructs were significant. Findings for Tanzania indicated insignificant results for ICTI and ISA and positive significant results for TMS and UA. The Ugandan data set indicated insignificant results for ISA and TMS and positive significant results for ICTI and UA.